Who Gets Ahead and Who Falls Behind During the Transition to High School? Academic Performance at the Intersection of Race/Ethnicity and Gender. (5th March 2018) - Sutton, April; Langenkamp, Amy G; Muller, Chandra; Schiller, Kathryn S
Abstract: Academic stratification during educational transitions may be maintained, disrupted, or exacerbated. This study marks the first to use national data to investigate how the transition to high school (re)shapes academic status at the intersection of race/ethnicity and gender. We seek to identify the role of the high school transition in shaping racial/ethnic and gender stratification by contextualizing students' academic declines during the high school transition within the longer window of their educational careers. Using Add Health, we find that white and black boys experience the greatest drops in their grade point averages (GPAs). We also find that the maintenance of high academic grades between the eighth and ninth grades varies across racial/ethnic and gender subgroups; higher-achieving middle school black boys experience the greatest academic declines. Importantly, we find that white and black boys also faced academic declines before the high school transition, whereas their female student peers experienced academic declines only during the transition to high school. We advance current knowledge on educational stratification by identifying the transition to high school as a juncture in which boys' academic disadvantage widens and high-achieving black boys lose their academic status at the high school starting gate. Our study also underscores the importance of adopting an intersectional framework that considers both race/ethnicity and gender. Given the salience of high school grades for students' long-term success, we discuss the implications of this study for racial/ethnic and gender stratification during and beyond high school.